Caregivers' estimate of early childhood developmental status in rural Uganda: a cross-sectional study. Issue 6 (22nd June 2021) - Bonney, Emmanuel; Villalobos, Michele; Elison, Jed; Sung, Sooyeon; Wosu, Adaeze; SSemugabo, Charles; Pariyo, George; Kajungu, Dan; Rutebemberwa, Elizeus; Hyder, Adnan A; Gibson, Dustin
Abstract : Objective: To characterise developmental milestones among young children living in rural communities in Uganda. Design: Cross-sectional study. Setting: Iganga-Mayuge Health and Demographic Surveillance Site in rural eastern Uganda. Participants: A total of 720 caregivers of children aged 3–4 years old from a health and demographic surveillance site in rural eastern Uganda were recruited into this study. Caregivers reported on their child's developmental skills and behaviours using the 10-item Early Childhood Development Index (ECDI) developed by UNICEF. Childhood development was characterised based on the ECDI's four domains: literacy-numeracy, learning/cognition, physical and socioemotional development. As an exploratory analysis, we implemented a hierarchical agglomerative cluster analysis to identify homogenous subgroups of children based on the features assessed. The cluster analysis was performed to identify potential subgroups of children who may be at risk of developmental problems. Results: Between November 2017 and June 2018, 720 caregivers of children aged 3–4 years completed the ECDI. The proportions of children at risk of delay in each domain were as follows: literacy-numeracy: 75% (n=538); socioemotional development: 22% (n=157); physical: 3% (n=22); and cognitive: 4% (n=32). The cluster analysis revealed a three-cluster solution that included 93% of children assigned to a low-risk group, 4% assigned to a moderate-risk group and 3% assigned to a high-risk group characterised by low scores in almost all domains. Conclusion: The findings suggest that a high proportion of children in rural eastern Uganda demonstrate poor literacy-numeracy skills. These results underscore the need to improve population-based screening and intervention efforts to improve early childhood developmental outcomes, particularly in literacy and socioemotional domains, in low-income and middle-income countries such as Uganda.